Pharmacokinetics of hydroxymethylnitrofurazone and its parent drug nitrofurazone in rabbits - Nogueira Filho, Marco Antonio Ferraz; Padilha, Elias Carvalho; Campos, Michel Leandro de; Machado, Diego Vinicius de Pontes; Davanço, Marcelo Gomes; Pestana, Kelly Christina; Chin, Chung Man; Peccinini, Rosângela Gonçalves [UNESP] (Drug Metabolism Letters, 2013)
The prodrug hydroximethylnitrofurazone (NFOH) presents antichagasic activity with greatly reduced toxicity compared to its drug matrix nitrofurazone (NF). Besides these new characteristics, the prodrug was more active against the parasite T. cruzi amastigotes. These advantages make the prodrug a possible therapeutic alternative for the treatment of both acute and the chronic phase of Chagas disease. However, the knowledge of pharmacokinetic profile is crucial to evaluate the feasibility of a new drug. In this study, our objective was to evaluate the in vivo formation of NF from the NFOH single administration and to evaluate its pharmacokinetic profile and compared it to NF administration. A bioanalytical method to determine the NF and NFOH by LCMS/MS was developed and validated to perform these investigations. Male albino rabbits (n=15) received NF intravenously and orally in doses of 6.35 and 63.5 mg / kg respectively, and NFOH, 80.5 mg / kg orally. The serial blood samples were processed and analyzed by mass spectrometry. The system operated in positive and negative modes for the analites determination, under elution of the mobile phase 50:50 water: methanol. The administration of NFOH allowed the calculation of pharmacokinetic parameters for the prodrug, and the NF obtained from NFOH administration. Using the pharmacokinetic profile obtained from the NF i.v. administration, the oral bioavailability of NF from the administered prodrug was obtained (60.1%) and, as a key parameter in a prodrug administration, should be considered in future studies. The i.v. and oral administrations of NF differ in the constant of elimination (0.04 vs 0.002) and elimination half-life (17.32 min vs 276.09 min) due to the low solubility of the drug that hinders the formation of molecular dispersions in the digestory tract. Still, there was observed no statistical differences were observed between the pharmacokinetic parameters of orally administered NF and NF obtained from NFOH. The calculated area under the curve (AUC 0-∞) showed that the exposure to the parental drug was fairly the same (844.79 vs 566.44) for NF and NF obtained from the prodrug administration. The tendency to higher NF's mean residence time (MRT) as observed in the prodrug administration (956.1 min vs 496.3 min) guarantees longer time for the action of the drug and it allows the expansion of the administration intervals. These findings, added with the beneficial characteristics of the prodrug encourage new efficacy tests towards the clinical use of NFOH.
Keywords: Chagas disease; hydroxymthylnitrofurazone; nitrofurazone; pharmacokinetics; preclinical studies